Modeling leaf and crop water use efficiency of rainfed Cotton: Interplay of environmental and biophysical drivers - Shreedevi Moharana; Syam Chintala; BVN P. Kambhammettu (Agricultural Water Management)
Being the key eco-hydrologic trait linking carbon fixation (photosynthesis) and water consumption (transpiration), water use efficiency (WUE) plays a vital role in the plant-atmosphere continuum. However, ecological drivers and scaling relations on WUE represented at different scales is poorly understood. This study is aimed at simulating WUE of rainfed Cotton at leaf ‘WUEL’ and crop ‘WUEC’ scales, and further investigates the role of environmental and biophysical factors on WUE dynamics. The simulated leaf and crop WUE fluxes were used to establish the scaling relations. Stomatal conductance ‘gs’ and WUEL of Cotton leaves exposed to ambient CO2 are simulated using modified Ball-Berry model with instantaneous gas exchanges measured around noon used to validate the model. We observed a large diurnal (4.3 ± 1.9 mmolCO2 mol−1H2O) and seasonal (5.16 ± 1.51 mmolCO2 mol−1H2O) variations in WUEL. Model simulated gs and WUEL are in agreement with measurements (ρ>0.5, RMSE<0.3). Meteorological, phenologic, and management conditions during the crop cycle were used to simulate WUEC using FAO-AquaCrop. Model calibration was performed with gravimetric measurements of soil water content (ρ = 0.95, RMSE = 21.8) and eddy covariance (EC) measurements of evapotranspiration (ρ = 0.57, RMSE = 0.88). Seasonal variations in WUEC ranged from 1.7 to 7.3 kg/m3 during crop cycle. We observed strong linear relations between WUEL and WUEC during maturity stage (ρ = 0.84) followed by growth stage (ρ = 0.75). Eight climate and biophysical factors were considered to see their dependence on WUE at both scales. Our results conclude that WUEL is governed by soil moisture content (ρ = −0.75) and leaf area index (ρ = 0.57), whereas WUEC is controlled by canopy cover (ρ = 0.86) and vapor pressure deficit (ρ = −0.63). Our findings can help in developing effective water management strategies to improve WUE in rainfed Cotton.